Promoting Career Maturity through Cognitive Behavior Therapy in Group Counseling: A Pathway to Informed Decision-Making for Students - Khofifah, Nur; Netrawati, Netrawati; Ardi, Zadrian (Jurnal Bimbingan dan Konseling Terapan, 2023)
This article explores the potential of Cognitive Behavior Therapy (CBT) in group counseling to enhance career maturity and informed decision-making among students. The concept of career maturity, defined as an individual's readiness and capability to make informed career decisions, is crucial in guiding students through the career decision-making process. Career guidance programs have been recognized as instrumental in fostering career maturity and informed decision-making. The integration of CBT in group counseling has been proposed as an effective approach to enhance career maturity. This systematic literature review examined various sources to gather empirical evidence and theoretical perspectives on the topic. The findings indicate that CBT-based group counseling sessions significantly improve students' career maturity and decision-making skills. The cognitive restructuring process inherent in CBT helps students challenge negative thoughts and develop confidence in their career decisions. The supportive environment of group counseling encourages interaction and mutual learning among participants. Despite promising results, the study acknowledges limitations, such as reliance on self-reported measures. It recommends further research to explore long-term effects and encourages educational institutions and career counselors to incorporate CBT-based group counseling sessions into their programs. The article contributes to the expanding body of knowledge on CBT's role in enhancing career maturity and decision-making and provides insights for educators, counselors, and researchers in this field.